Geographic and demographic features of neuroendocrine tumors in the United States of America: A population‐based study. Issue 4 (12th November 2019) - Gosain, Rohit; Ball, Somedeb; Rana, Navpreet; Groman, Adrienne; Gage‐Bouchard, Elizabeth; Dasari, Arvind; Mukherjee, Sarbajit
Abstract : Background: The incidence of neuroendocrine tumors (NETs) is rapidly rising. There are very few studies investigating the role of sociodemographic factors in NETs. This study was aimed at examining how geographic and sociodemographic characteristics shape outcomes in the NET population. Methods: A retrospective analysis using the Surveillance, Epidemiology, and End Results database was performed, and the NET patient population from 1973 to 2015 was studied. Univariate and multivariable analyses were performed to evaluate patients' disease‐specific survival (DSS) and overall survival (OS). Geographic and sociodemographic factors, including the location of residence (urban area [UA] vs rural area [RA]), sex, race, insurance status, and marital status, were included in the analysis. Results: A total of 53, 034 patients (5517 in RAs and 47, 517 in UAs) were included in the analysis. The incidence of NETs was found to be rising in both RAs and UAs but more rapidly in RAs (with the highest incidence in 2006‐2015: 5.93 per 100, 000 in RAs vs 4.10 per 100, 000 in UAs). Patients from RAs presented at advanced stages in comparison with patients from UAs (regional, 18% vs 16%; distant, 15% vs 13%; P  < .01). In the multivariable model, RA patients had a trend toward poorer OS (hazard ratio, 1.05; P  = .053) in comparison with UA patients. The multivariable analysis showed significantly worse DSS and OS for uninsured, single, and male patients in comparison with insured, married, and female patients, respectively. Conclusions: This study has identified sociodemographic disparities in NET outcomes. Access to health care could be a potential contributing factor, although differences in environmental exposure, health behavior, and tumor biology could also be responsible. Abstract : The incidence of neuroendocrine tumors is rapidly rising, with few studies investigating the role of sociodemographic factors in neuroendocrine tumors. This study identifies sociodemographic disparities and shows that urban patients have a trend towards better disease‐specific survival and overall survival than rural patients; in addition, it demonstrates significantly worse disease‐specific survival and overall survival for uninsured, single, and male patients in comparison with insured, married, and female patients, respectively.